The Spatial Dimension of Import Competition - Joakim Gullstrand; Polina Knutsson (Lund University, School of Economics and Management, Department of Economics, 2019)
Exposure to international competition on a country level has been shown to improve the efficiency of domestic producers. We contribute to this literature by assessing whether the distance between producers and importers, within a country, matters for import competition effects at product level. Using detailed geographical information about the location of all manufacturing firms in Sweden during the period 2005–2014, we find strong evidence of an increased efficiency in the domestic production when imports surge, but that the effect diminishes with the distance between the producer and the importer. In addition to the importance of the geographical pattern within a country, we find that the average effect of import competition conceals large variations across firms and products. Highly productive firms respond to import competition by further improving efficiency, which, in turn, is transmitted to both a lower price and a higher markup. Firms are also more likely to drop fringe products while keeping core ones. Products undercut by low import prices in their proximity respond by lowering prices only, although highly efficient products resist this by a more pronounced improvement in the marginal cost, which, in turn, is transmitted to both a lower price and a higher markup.
Keywords: F14; 330; Import competition; distance; firm-product performance